Relationship between net photosynthesis and leaf respiration in Mediterranean evergreen species - Gratani, L; Varone, L; Catoni, R (Photosynthetica, 2008)
The relationship between net photosynthetic (PN) and leaf respiration (R) rates of Quercus ilex, Phillyrea latifolia, Myrtus communis, Arbutus unedo, and Cistus incanus was monitored in the period February 2006 to February 2007. The species investigated had low R and PN during winter, increasing from March to May, when mean air temperature reached 19.2 °C. During the favourable period, C. incanus and A. unedo had a higher mean PN (16.4±2.4 µmol m −2 s −1 ) than P. latifolia, Q. ilex, and M. communis (10.0±1.3 µmol m −2 s −1 ). The highest R (1.89±0.30 µmol m −2 s −1 , mean of the species), associated to a significant PN decrease (62 % of the maximum, mean value of the species), was measured in July (mean R/PN ratio 0.447±0.091). Q10, indicating the respiration sensitivity to short-term temperature increase, was in the range 1.49 to 2.21. Global change might modify R/PN determining differences in dry matter accumulation among the species, and Q. ilex and P. latifolia might be the most favoured species by their ability to maintain sufficiently higher PN and lower R during stress periods.
Keywords: arbutus; cistus; Myrtus; Phillyrea; Q10; Quercus; seasonal course; temperature.

Environmental induced variations in leaf dark respiration and net photosynthesis of Quercus ilex L. - Gratani, L; Varone, L; Bonito, A (Photosynthetica, 2007)
The relationships between dark respiration rate (RD) and net photosynthetic rate (PN) in Quercus ilex L. shrubs growing at the Botanical Garden in Rome were analysed. Correlation analysis of the data sets collected in the year 2006 confirmed the dependence among the considered leaf traits, in particular, RD was significantly (p<0.05) correlated with PN (r = 0.40). RD and PN increased from March to May [1.40±0.10 and 10.1±1.8 μmol(CO2) m –2 s –1 mean values of the period, respectively], when air temperature was in the range 14.8–25.2 °C, underlining the highest metabolic activity in the period of the maximum vegetative activity that favoured biomass accumulation. On the contrary, the highest RD [1.60±0.02 μmol(CO2) m –2 s –1 ], associated to the lowest PN rates (44 % of the maximum) and carbon use efficiency (CUE) in July underlined the mobilization of stored material during drought stress by a higher air temperature (32.7 °C).
Keywords: carbon use efficiency; Leaf temperature; seasonal course

Relationship between photosynthetic activity and chlorophyll content in an isolated Quercus ilex L. tree during the year - Gratani, L; Pesoli, P; Crescente, M F (Photosynthetica, 1998)
The relationship between chlorophyll (Chl) content and net photosynthetic rate (PN) in an isolated Quercus ilex tree, growing inside Villa Pamphili Park in Rome, was explored. The highest Pn was in March, May and September (10.1 umol.m-2.s-1, maximum rate). Pn decreased by 65% (with respect to the yearly maximum) when leaf temperature reached 34ºC, and by 50% when leaf temperature was 9ºC. The highest Chl contents were in April, October [1.47g.kg-1 (d.m.), maximum value], and December. The lowest Chl content was found in July (0.78 g.kg-1). The decrease of PN in July was in close connection with the decrease of Chl content. On the contrary, the high Chl content during winter did not correspond with PN of this season. Discordances between Chl content and PN over the year influenced the regression analysis, which although positive did not show very high correlation coefficients (r=0.79. The high Chl (a+b) content during most of the year indicated that the photosynthetic apparatus remained basically intact also during stress periods.
Keywords: net photosynthetic rate; oak; Regression Analysis; seasonal course; Stomatal conductance